Analysis of exosome-derived microRNAs as early biomarkers of lipopolysaccharide-induced acute kidney injury in rats - Da-Silva, Carolina Carvalho Serres; Anauate, Ana Carolina; Guirao, Tatiana Pinotti; Novaes, Antônio da Silva; Maquigussa, Edgar; Boim, Mirian Aparecida (Frontiers in Physiology, 2022)
Sepsis contributes to the high prevalence of acute kidney injury (AKI), which mainly occurs in hospitalized patients. The delay in AKI detection is a risk factor for death and chronicity; thus, early diagnosis is essential for initiating proper treatment strategies. Although serum creatinine is used as biomarker, it is increased in plasma serum creatinine only at late stages of AKI. MicroRNAs (miRNAs), a class of noncoding RNAs responsible for gene regulation, can be found in biological fluids within vesicles such as exosomes and may be promising tools for the early detection of AKI. We aimed to identify potential blood miRNAs that can be used as early biomarkers of sepsis-induced AKI in rats. Adult male Wistar rats received a single dose of lipopolysaccharide (LPS). The earliest significant increase in serum creatinine was detected 4 h after LPS administration. To evaluate whether miRNAs could act as early biomarkers, blood samples were collected before and 2 h after LPS infusion. Serum NGAL levels were used as a comparative marker. Serum miRNAs were derived from exosomes, and their expression were evaluated by the PCR array. miR-181a-5p and miR-23b-3p showed higher expression in LPS-treated rats than in the control animals (p<0.05). Bioinformatics analysis showed that both miRNAs target molecules associated with transcription factors that regulate genes related to proinflammatory cytokines. Considering that LPS activates transcription factors that lead to the production of proinflammatory cytokines, possible premature changes in the serum levels of miR-181a-5p and miR-23b-3p may be used to identify sepsis-induced AKI earlier.